(untitled) (Al-Aasar, 2025)
Children are considered one of the greatest blessings and trusts granted by Allah Almighty in Islam. Their protection, upbringing, and proper moral and educational training are the foremost responsibilities of parents and society. The Qur’an repeatedly emphasizes the sanctity of children’s lives, condemning all forms of oppression and violence against them, and commands mercy, kindness, and justice in their treatment. The Prophet Muhammad (peace be upon him) practically demonstrated these teachings by showing profound affection and compassion towards children, making it a model for Muslim families and communities. This research critically analyzes the prohibition of child abuse and the protection of children’s rights in the light of Qur’ānic injunctions, Prophetic Sunnah, classical jurisprudence, and contemporary social challenges. It further highlights that while Islamic jurisprudence allows disciplinary measures only within corrective limits, any form of violence that inflicts harm, humiliation, or psychological trauma is strictly forbidden. The study also integrates modern psychological findings that demonstrate the adverse impacts of violence on children’s personality development, self-confidence, and social behavior. By correlating Islamic principles with modern social and educational research, this paper underscores the universality and timelessness of Islamic teachings on child protection. It concludes that safeguarding children’s rights is not only a religious duty but also a collective social responsibility. Finally, the study suggests practical recommendations for parents, educators, policymakers, and society at large to ensure that children are nurtured in an environment of love, dignity, and holistic care.